Recovery of zooplankton diversity in a restored Mediterranean temporary marsh in Don˜ ana National Park (SW Spain) - Badosa, Anna; Frisch, Dagmar; Arechederra, Arantza; Serrano Martín, Laura; Green, Andy J. (Hydrobiologia, 2010)
Over 30 years after drainage for agricul- ture, a 2700 ha temporary marshland was recently restored in Don˜ ana National Park. We describe the recovery of zooplankton communities (copepods, cladocerans and rotifers) in 47 new temporary ponds excavated as part of the restoration project during the first two hydroperiods (April 2006 and 2007), and compare them to those of eight reference sites in the surrounding marshland. Major changes in the species composition and abundance occurred in new ponds between years. While rotifers and cyclopoid cope- pods dominated in terms of number of individuals in 2006, calanoid copepods and cladocerans were the most abundant groups in 2007. Rotifer species richness was significantly lower in 2007, but there was an increase in Simpson and b-diversity in 2007 owing largely to a dramatic decline in the abundance of Hexarthra cf. fennica (rare in reference sites) from 93% of all rotifer individuals in new ponds in 2006 to only 32% in 2007. In contrast, species richness of copepods and cladocerans was significantly higher in new ponds in 2007, but there were no changes in Simpson diversity. b-Diversity of cladocerans was also significantly higher in 2007. In 2006, the species richness of cladocera and copepods was significantly lower in new ponds than in reference sites, but by 2007 there were no differences in richness or Simpson diversity. Overall, 7 copepod, 13 cladoceran and 26 rotifer taxa were recorded in new ponds, including 80% of taxa recorded in reference sites. These results indicate that zooplankton communities can be rapidly restored in Mediterranean temporary wetlands, at least when large source populations in the surrounding area reduce dispersal limitation. They also illustrate the importance of comparing different metrics of richness and diversity in studies of zooplankton restoration. Peer reviewed